Investigating changes in calcium, phosphorus, alkaline phosphatase, and 25-hydroxy Vitamin D after surgical repair of fractures of femur or tibia : Ca, PHP, ALP , and 25(OH)D Changes after femur or tibia surgery - Sobhani Eraghi, Amir; Saberi, Saba; Molazemsanandaji, Borzouyeh; Ghaznavi, Alireza (Acta Biomedica Atenei Parmensis, 2020)
Background: The recovery of long bones after fracture requires a specific process to restore the natu-ral bone anatomy as well as its proper function. Changes in calcium, phosphorus, alkaline phosphatase and 25-hydroxy vitamin D can be justified either in the fracture process or in the repair procedure. The aim of this sectional study is to investigate changes in all these compounds after the surgical repair of fractures of femur and tibia bones. Materials and Methods: A random sample of 68 patients was selected from whom referring to a hospital with fractures of femur or tibia and candidate for repair surgery. The mentioned bone markers were measured at the time after surgery, six and twelve weeks after the surgery with laboratory-specific kits. A p-value, lower than 0.05, was considered to be statistically significant. Result: Of the patients, 34 were with fractures of femur and 34 were with fractures of tibia, equally. The patients were aged 2 to 69 with a mean age of 27.93 ± 14.8 years old. The means of calcium (p = 0.001) and phosphorus (p = 0.014) at three intervals were statistically significant difference. In contrast, the means serum alkaline phosphatase and vitamin D levels did not show any significant changes over time (p = 0.042). Conclusion: In conclusion, the means of calcium and phosphorus over the follow-up were statistically significant. The observed difference of vitamin D after the surgery, as well the level of alkaline phosphatase for femoral fracture between male and female are one of our important findings. (www.actabiomedica.it)